Irinotecan and capecitabine as second-line treatment after failure for first-line infusional 24-h 5-fluorouracil/folinic acid in advanced colorectal cancer: a phase II study - Hofheinz, Ralf-Dieter; Gnad-Vogt, Ulrike; Wein, Axel; Saußele, Susanne; Kreil, Sebastian; Pilz, Lothar R.; Hehlmann, Rüdiger; Hochhaus, Andreas (Anti-cancer drugs, 2005)
The efficacy of combination therapy with irinotecan and capecitabine has been demonstrated for the first-line treatment of metastatic colorectal cancer (MCRC). The aim of this trial was to evaluate the efficacy and safety of this combination in MCRC as second-line treatment after failure of 24-h infusional 5-fluorouracil (5-FU24h) and folinic acid (FA). Patients pre-treated with 5-FU24h/FA were recruited at two institutions to receive 6×weekly irinotecan 70 mg/m2 and capecitabine (1000 mg/m2 b.i.d. days 1-14 and 22-35). Courses were repeated on day 50. In elderly patients (>65 years) a 20% dose reduction of both drugs was scheduled. Twenty-eight patients [M/F 20/8; median age 65 years (range 44-79); median ECOG score 1] were enrolled. The most frequent sites of metastases were liver, n=20, lymph nodes and lungs, n=10, respectively. Half of the patients had two or more metastatic sites. A total of 71 treatment courses (median 2, range 1-8) were administered. Main toxicities [worst per patient (%); CTC grade 1/2/3/4] were: anaemias 18/14/-/-; leukocytopenia 11/21/-/-; thrombocytopenia 11/-/-/-; diarrhea 18/36/21/-; nausea/vomiting 43/29/4/-; mucositis 4/11/-/-; alopecia 7/25/-/-; hand-foot syndrome 7/21/-/-; fatigue 14/14/-/-; renal insufficiency (caused by diarrhea and exsiccosis) -/-/-/7. Dose intensity in the first course was [median/mean (%)]: irinotecan 92/83; capecitabine 88/82. Twenty-three patients are evaluable for response analysis (five did not complete the first course): three patients showed partial remissions (13%) and 11 patients had stable disease (48%). Median time to progression was 3.0 months for the total population (range 1.4-17.3) and 6.5 months for responders (partial response plus no change). Seventy-four percent of the patients received a third-line therapy. Overall survival was 15.7 months calculated from the start of study treatment. Second-line therapy with irinotecan and capecitabine yielded a tumor control in 61% of patients with MCRC. Efficacy and toxicity data are comparable to 5-FU/irinotecan combinations, although the likelihood of severe diarrhea appears to be higher with capecitabine/irinotecan.
Gesehen am 12.05.2022